Study of the effect caused by rapid disjunction with Miniscrew Assisted Rapid Palatal Expansion (MARPE), im the alveolar bone in molar regions: In sílico (Research, Society and Development, 2025)
Objective: To determine the effect caused on the alveolar bone in the molar region by rapid disjunction with MARPE. Methodology: The present research was developed with the objective of evaluating the effect caused on the alveolar bone in molar regions by rapid disjunction with MARPE, in silico, and in a documentary research from a direct source (tomography) and with the support of narrative review. The research was carried out by the specialization course in orthodontics of the Faculty of the Midwest of São Paulo (FACOP) – Maceió nucleus. Results: After the analysis of the three cone beam computed tomography (CBCT) scans, it was possible to verify the decrease in alveolar bone thickness in the vestibular region of molars. Conclusion: From this in silico study, it can be concluded that the orthodontic effect of the rapid maxillary expansion produced by MARPE stimulated a reduction in the alveolar bone in the upper molar region. It is likely that, after the retention period, the dimensions evaluated in this study will be different, since there is bone remodeling after the active phase of maxillary disjunction has ended.